Kualitas Ekstrak Akasia dari Berbagai Lokasi di Indonesia dan Efek Penambahan Aditif pada Daya Rekatnya - Pari, Rohmah; Aini, Erlina Nurul; Lubis, Yunida Syafriani; Prastiwi, Dina Alva; Santoso, Adi (BRIN Publishing, 2025)
The tannin characteristic of plants is often influenced by their planting location. The characteristic of tannin potentially affects the quality of tannin-based adhesive. The addition of extender and hardener also influences the quality of tannin adhesive. In this study, we investigated the characteristics of Acacia mangium tannin extract produced from bark obtained from various locations in Indonesia, as well as the bonding quality of tannin adhesive with the addition of an extender and hardener. The objective of this research was to understand the difference in mangium tannin characteristics from different locations and the effect of extender and hardener addition on the bonding strength of acacia tannin adhesive. The Acacia mangium wood barks were obtained from Parung Panjang, Probolinggo, Pontianak, and Muara Enim. The amounts of extender and hardener added were 0%, 2.5%, 5%, 7.5%, 10%, and 0%, 0.5%, 1%, 1.5%, 2%, respectively. The evaluation of mangium tannin bark extract was conducted using the solid content and stiasny number tests. The bonding strength of the tannin adhesive was evaluated through shear strength and wood failure tests of sengon laminated wood. The two-ply sengon laminated wood was fabricated under the following conditions: a glue spread rate of 170 g/m², a cold-press time of 24 hours, and a pressure of 12 kg/cm². Mangium tannin bark extract from Parung Panjang has the best characteristics for adhesive production, i.e., 5.70% solid content and 200.63% stiasny number. The extender and hardener amounts of 7.5% and 1.5%, respectively, produced optimum properties for dry shear strength and wood failure, which meet the JAS No. 234 requirement, i.e., 112.31 kg/cm² and 98–100%, respectively.